ROBOT CATTLE AND POULTRY FEEDER - Dr.V.A NARAYANA, B.ARCHANA, K.RAVI KIRAN,K.ARCHANA, K.NAVEEN, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Many people in developing countries still use driven machine for cutting cattle feed and distributing it manually. These machines become less safe to the person while operating and it requires more skilled labour for operating. The main barriers are lack of labour and blockage of grass creates feed interference. Now-a- days efforts have been made by developing countries to promote automation in feeding systems. Various types of feeding machines are available in the market but these technologies operate at a very low efficiency and consume more power and leads to the wastage of feed (crops). A number of different types of AFS are currently used, because of their potential of reducing labour time and workload as well as more flexible working time. Furthermore, farmers focus on the benefits for their animals, where Food and feeding are the important elements for growth and production. The cattle need to be fed. It is a simple statement, but one that resonates with every cattle producer. To make this necessary task easier for farmers, the concept of automatic cattle feeding system came into existence. Automatic Cattle Feeding System is a robotic feeding system which consists of a battery operated robotic vehicle that is capable of feeding an equal amount of feed. All the existing equipment are largely for large scale cattle and poultry farms. But there is no machine for small scale cattle or poultry farms where the human labour is used for feeding the cattle. Our project aims to feed small scale Dairy and Poultry farms as there is no advanced technology that makes things easier for the farmers. Our project can help the farms to cut excess Human labour and also excess strain that affects their body.